2021
DOI: 10.3389/fcell.2021.749153
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Parasites Hijack Host Receptors From Exosomes to Capture Lipoproteins

Abstract: Malaria parasites cannot multiply in host erythrocytes without cholesterol because they lack complete sterol biosynthesis systems. This suggests parasitized red blood cells (pRBCs) need to capture host sterols, but its mechanism remains unknown. Here we identified a novel high-density lipoprotein (HDL)-delivery pathway operating in blood-stage Plasmodium. In parasitized mouse plasma, exosomes positive for scavenger receptor CD36 and platelet-specific CD41 increased. These CDs were detected in pRBCs and interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Data from the malaria literature suggest that decreases in HDL associated with babesiosis may be directly related to the growth of the parasite. Multiple studies have shown that Plasmodium spp., Apicomplexans protozoa that are closely related to Babesia spp., does not possess the biosynthetic pathway for de novo synthesis of cholesterol and must scavenge this important molecule from host hepatocyte and erythrocyte membranes [22][23][24]. In humans, acute malaria infections are associated with lower LDL and HDL and the total cholesterol [25].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the malaria literature suggest that decreases in HDL associated with babesiosis may be directly related to the growth of the parasite. Multiple studies have shown that Plasmodium spp., Apicomplexans protozoa that are closely related to Babesia spp., does not possess the biosynthetic pathway for de novo synthesis of cholesterol and must scavenge this important molecule from host hepatocyte and erythrocyte membranes [22][23][24]. In humans, acute malaria infections are associated with lower LDL and HDL and the total cholesterol [25].…”
Section: Discussionmentioning
confidence: 99%
“…DIC is associated with more severe disease and cerebral malaria, and as such, high mortality [ 206 ]. In malaria infection, both in people ( Plasmodium falciparum and vivax ) and in mice ( Plasmodium berghei ) there are higher numbers of circulating EVs and PEVs [ 70 , 71 , 207 ]. PEVs in malaria positively correlate with clinical symptoms, including fever, cerebral malaria, coma depth, thrombocytopenia, and length of symptoms [ 70 , 71 ].…”
Section: Platelet-derived Extracellular Vesicles In Infectious Diseasesmentioning
confidence: 99%
“…PEVs in malaria affect coagulation by interacting with and activating other cell types. First, PEVs can bind to and be taken up by parasitized red blood cells (pRBC) [ 145 , 207 ]. In doing so, the PEV transfers both cholesterol and platelet antigens to the surface of the pRBC.…”
Section: Platelet-derived Extracellular Vesicles In Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid synthesis throughout the life cycle of malaria parasites range from fatty acid synthesis to lipid droplet formation with neutral lipids 2,4 . Although most lipid classes can also be scavenged from the host cytoplasm and extracellular environment, parasites must maintain a stable balance of fatty acids and phospholipid and neutral lipid synthesis to meet the diverse needs of these molecules at different stages and environments 58 .…”
Section: Introductionmentioning
confidence: 99%